Data Science, Human-Centered Computing, and Intelligent Technologies - Hajian, Aram; Baloian, Nelson; Inoue, Tomoo; Luther, Wolfram (Logos Verlag Berlin, 2022)
In August 2022, researchers and developers from Armenia, Chile, Germany, and Japan met at the American University of Armenia for the third edition of the CODASSCA Workshop on Collaborative Technologies and Data Science in Smart City Applications, co-organized with a Summer School on Artificial Neural Networks and Deep Learning. This book presents their contributions on intelligent technologies in data science and human-centered computing.